Prospective clinical evidence from over 1,000 pan-cancer patients: a complement to fosaprepitant in the prevention of chemotherapy-induced nausea and vomiting - Lijuan He; Jize Wang; Weigao Pu; Haiyuan Li; Ben Liu; Zhuanfang Wang; Qinying Han; Yunpeng Wang; Bo Xu; Jike Hu; Guodong Sun; Hao Chen (BMC Cancer)
Abstract Background Chemotherapy-induced nausea and/or vomiting (CINV) is an intractable adverse effect of anticancer drugs. Although prophylactic use of fosaprepitant may be effective in reducing CINV, there is a lack of studies evaluating the application of fosaprepitant in real world. Aims and methods This study prospectively observed the effectiveness and safety for the prophylaxis of CINV in a real-world clinical setting. A single dose fosaprepitant 150 mg was intravenously administered to enrolled patients 30 min prior to the chemotherapy drug. Initial data were recorded and patients were followed for 120 h (5 days). The primary endpoint is the complete response (CR) rate and the incidence of serious adverse events (SAEs). The second endpoint is the use of rescue therapy. We also performed stratified analyses to investigate the impact of different factors on fosaprepitant for the prevention of CINV in the acute phase. Results Between March 2021 to August 2021, 1001 patients were enrolled in this study. CR was 77.32%, 93.61%, and 76.72% for vomiting control in 0–24 h, 24–120 h, and 0–120 h respectively, and 97.4%, 99.1%, and 96.9% for nausea control. No SAEs were recorded. 23.48% or 3.1% of patients needed rescue therapy for vomiting or nausea control respectively, most of which occurred in the acute phase. CR rate decreased with increasing emetogenicity of chemotherapeutic agents. Conclusions Single-dose fosaprepitant has shown good performance in real-world clinical practice. This study is the first to prospectively evaluate the efficacy and safety of fosaprepitant for the prevention of CINV in a real-world clinical setting and may be a good complement to the clinical data.